Assessment of the Concentration and Structure of the Bioeconomy: The Regional Approach - Aina Muska; Dina Popluga; Irina Pilvere (Emerging Science Journal, 2023)
The bioeconomy is seen as crucial for achieving a climate-neutral Europe by 2050; therefore, it is important to monitor and illustrate the performance and trends of the bioeconomy development not only at state level but also in regions. The research aims to develop a methodology for the identification of bioeconomy concentration and the structure of bioeconomy enterprises at a regional level. The methodology of the research is based on four main steps: (1) defining the framework of bioeconomy enterprises; (2) setting data sources and research limitations; (3) estimating the bio-based share of bioeconomy industries; (4) estimating a location quotient which provide data serving to assess the level of concentration of the factor analysed. The research is based on the analysis of 119 municipalities and 30 387 bioeconomy enterprises by using a location quotient. The research results revealed that the municipalities could be classified into three groups according to the concentration of the bioeconomy. Such a classification of municipalities allowed us to identify the strengths and weaknesses of each municipality in the field of bioeconomy and potential development possibilities. The novelty of the research provides a methodological background for municipal-level monitoring of the bioeconomy and suggestions for improving the uneven development of the bioeconomy. Doi: 10.28991/ESJ-2023-07-01-05 Full Text: PDF